2014
DOI: 10.2478/pjct-2014-0069
|View full text |Cite
|
Sign up to set email alerts
|

The effect of selected supercritical CO2 plant extract addition on user properties of shower gels

Abstract: The formulations of washing cosmetics i.e. shower gels, containing extracts obtained during supercritical CO 2 extraction process as active ingredient, were developed. The subject of the study was the analysis of the physicochemical and user properties of the obtained products. In the work supercritical CO 2 extracts of black currant seeds, strawberry seeds, hop cones and mint leafs were used. The formulation contains a mixture of surfactants (disodium cocoamphodiacetate, disodium laureth sulfosuccinate, cocoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…In cosmetics, hops are used in bath lotions, among others [80]. Vogt et al [17] used supercritical CO 2 extracts of hop cones to formulate shower gels, and the results obtained showed that their addition enhanced their skin-conditioning properties due to their content in bioactive ingredients. Moreover, the formulations containing the extract of hop cones present compounds to treat oil and dandruff in hair.…”
Section: Current Applications Of Functional Molecules From Hopmentioning
confidence: 99%
See 2 more Smart Citations
“…In cosmetics, hops are used in bath lotions, among others [80]. Vogt et al [17] used supercritical CO 2 extracts of hop cones to formulate shower gels, and the results obtained showed that their addition enhanced their skin-conditioning properties due to their content in bioactive ingredients. Moreover, the formulations containing the extract of hop cones present compounds to treat oil and dandruff in hair.…”
Section: Current Applications Of Functional Molecules From Hopmentioning
confidence: 99%
“…Moreover, the formulations containing the extract of hop cones present compounds to treat oil and dandruff in hair. The use of hop extract in hair cosmetics is supported by its antifungal and antiseborrheic properties that decrease its brittleness, nourish it, give it shine, increase its strength, and prevent its loss [17].…”
Section: Current Applications Of Functional Molecules From Hopmentioning
confidence: 99%
See 1 more Smart Citation
“…SC-CO 2 has been used for the isolation of antioxidants and parabens from cosmetic products [ 130 ]. Vogt et al [ 131 ] investigated the extract of blackcurrant seeds, strawberry seeds, hop cones, and mint leaves obtained by SC-CO 2 for the production of shower gels and shampoo, and the result showed that those natural extracts could be used as ingredients in shower gels.…”
Section: Current Applications Of Supercritical Fluid Extractionmentioning
confidence: 99%
“…In cosmetics, hops are used in bath lotions, among others (Cieśliński and Idowski, 2003;Astray et al, 2020). Supercritical CO 2 extracts of hop cones were used to formulate shower gels resulting in enhanced skin-conditioning properties due to their content in bioactive ingredients (Vogt et al, 2014). Moreover, the formulations containing hop cone extract have compounds that treat oil and dandruff in hair.…”
Section: Polyphenols and Other Compoundsmentioning
confidence: 99%